Fuzzy Dice ranking index based on point wise values / Dr. Nazirah Ramli … [et al.] - Ramli, Dr. Nazirah; Mohamad, Prof. Dr. Daud; Mohamed, Noraini; Shohaimay, Fairuz; Abdul Razak, Nawal (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
A wide spectrum of methods has been proposed for ranking trapezoidal fuzzy numbers. However, most of the ranking methods have lengthy calculation which is tedious, very time consuming and leads to the difficulty of implementation. This study proposes fuzzy Dice index for ranking trapezoidal fuzzy numbers based on point wise values. Fuzzy Dice ranking index is unique as it employed Dice similarity measure index and rank' trapezoidal fuzzy numbers merely based on the point wise values of the trapezoidal fuzzy numbers. This index can rank both normal and non-normal' trapezoidal fuzzy numbers, which makes it applicable as a flexible decision-making tool for selection alternatives. It is also a valuable tool as it offers a potential commercialization benefits in terms of speeding up a decision-making process which in return will make the process economically feasible. Fuzzy practitioners will be benefited from this ranking index which gives a desired impact on economic activities that directly has a positive effect in quality of life.